Self-Assembly of [3]Catenane and [4]Catenane Based on Neutral Organometallic Scaffolds - Wu, Gui-Yuan; Zhu, Hong-Juan; Pan, Fang-Fang; Sheng, Xiao-Wei; Zhang, Ming-Rui; Zhang, Xianyi; Yao, Guangxin; Qu, Hang; Lu, Zhou (Frontiers in Chemistry, 2021)
Transition metal-mediated templating and self-assembly have shown great potential to construct mechanically interlocked molecules. Herein we describe the formation of bimetallic [3]catenane and [4]catenane based on neutral organometallic scaffold via the orthogonality of platinum‐to‐oxygen coordination-driven self-assembly and copper(I) template-directed strategy of a [2]pseudorotaxane. The structures of these bimetallic [3]catenane and [4]catenane were characterized by multinuclear NMR 1H and 31P spectroscopy, electrospray ionization time-of-flight mass spectrometry (ESI-TOF-MS). In addition, single-crystal X-ray analyses of the [3]catenane revealed two asymmetric [2]pseudorotaxane units inside the metallocycle. Tubular structures were showed through the stacking of individual [3]catenane molecules by means of the strong π-π interactions.